2020
DOI: 10.1080/09649069.2020.1796218
|View full text |Cite|
|
Sign up to set email alerts
|

The Meaning of Home for Children and Young People after Separation

Abstract: This paper explores 68 Australian children and young people's understandings of what 'home' means for them after their parents' separation. Home-a familiar yet complex concept of great personal and social significance-has been a research focus for many other disciplines but not family law. We found that home, as an idea and lived experience, was complex. Children and young people's descriptions of home conveyed an interaction of tangible and intangible dimensions. Home was rarely defined by children and young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Children's idea of home and family may hold several dimensions, including both affective and relational aspects, material aspects and biological relatedness (Campo et al, 2020; Rigg & Pryor, 2007). In interviews with children about their idea of home, Campo et al (2020) found that relationship dimensions stood out as more important for them, whereas material dimensions mattered most when these gave evidence of their parents' attentiveness to their needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's idea of home and family may hold several dimensions, including both affective and relational aspects, material aspects and biological relatedness (Campo et al, 2020; Rigg & Pryor, 2007). In interviews with children about their idea of home, Campo et al (2020) found that relationship dimensions stood out as more important for them, whereas material dimensions mattered most when these gave evidence of their parents' attentiveness to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Children's idea of home and family may hold several dimensions, including both affective and relational aspects, material aspects and biological relatedness (Campo et al, 2020; Rigg & Pryor, 2007). In interviews with children about their idea of home, Campo et al (2020) found that relationship dimensions stood out as more important for them, whereas material dimensions mattered most when these gave evidence of their parents' attentiveness to their needs. Furthermore, the children strongly emphasized safety as an important aspect of what constitutes a good home, which according to the authors, may be related to the fact that many of these children had experiences of violence in their homes and also of positive changes in their home life when the violence ended.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some studies, shared parenting can be received negatively because of the necessity that children always have to carry personal things from one house to the other, they are continually deprived of the other house, and they are concerned about what is going on in the other house during the time they stay at a parent (Gunsberg, 2019). The proximity of the residences of the mother and father after divorce is a positive parameter in giving the child a sense of home (Campo et al, 2020a).…”
Section: Meaning Of Home From Different Family Perspectives In Divorc...mentioning
confidence: 99%
“…The home phenomenon means higher stress, workload, and responsibility for the mother compared to the father (Mallett, 2004). There are not many studies focusing on the feeling at home process of the mother's role in the family during the divorce process (Campo et al, 2020a). Like children, mothers define the home phenomenon with emotions like love, comfort, and togetherness rather than physical shelter.…”
Section: Meaning Of Home From Different Family Perspectives In Divorc...mentioning
confidence: 99%
See 1 more Smart Citation